ANALISIS FINANSIAL USAHA TAMBAK SILVOFISHERY DAN NON SILVOFISHERY SERTA KONTRIBUSI USAHA TAMBAK TERHADAP PENDAPATAN RUMAH TANGGA - Indra Budiman; Kansih Sri Hartini; Agus Purwoko (Peronema Forestry Science Journal, 2016)
Mangrove forest area is currently very vulnerable to environmental changes such as ecological pressures that come from nature and people. Preservation of mangrove area is very necessary, however the need of people’s livelihood around the mangrove areas can not be ignored as well. Accordingly, a business pattern which combines mangrove area and community pond system is developed, It is well known as silvofishery. This study aims to assess the financial analysis of silvofishery system and non silvofishery system and analyze the contribution of the pond business to the total income of household. This research was conducted in October - December 2014 and was held in Paluh Manan Village, Hamparan Perak Sub-District, Deli Serdang District, North Sumatra Province. This research used census method which the informants were interviewed directly. Comparative result of the financial analysis pond system shows the NPV and BCR of silvofishery is higher than the NPV and BCR of non silvofishery, which means silvofishery is more profitable than non silvofishery. Silvofishery and non silvofishery pond sufficiently provide high annual revenue for domestic fish farmer/tenants. The amount of the revenue is 65.83% for silvofishery and 55.44 % for non silvofishery. Key words : financial analysis, silvofishery, non silvofishery, household income